The High Burden of Depression, Anxiety, and Stress among University Students in Southern Iraq: A Cross-Sectional Study - Al-Karagoly, Hassan; Al-attar, Zahraa; Al-asadi, Hjar; Al-Lahibi, Sajad; Al-Fartousi, Russul; Al-Jadry, Teeba; Bali, Menatallah; Al-Hasnawi, Baneen; Al-aboudi, Hanan; Al-fadliu, Zainab; Al-mosawi, Ali; Al-Aboudi, Zahraa; et al. (AUIQ Complementary Biological System, 2025)
University students often face significant academic, social, and environmental pressures, making them particularly vulnerable to psychological distress. Despite this, there is limited evidence regarding the prevalence and associated factors of mental health problems among university students in Iraq. Therefore, this study aimed to assess the prevalence and severity of depression, anxiety, and stress in this population and to examine their associations with sociodemographic characteristics, insomnia, internet use, and physical activity. A cross-sectional study was conducted among Iraqi university students using a structured questionnaire, including the DASS-21, Insomnia Severity Index, and Internet Addiction Test. Descriptive and inferential statistics were used to analyze the data and identify associations between mental health outcomes and participant sociodemographic characteristics. A total of 690 university students were recruited in this study. The majority of participants were female, aged 2123 years, single, and enrolled in medical-related fields. The prevalence of depression, anxiety, and stress was 69.9%, 74.1%, and 62.2%, respectively. Female students, those from private universities, and participants without health insurance reported significantly higher psychological distress. Insomnia was a strong predictor of all depression, anxiety, and stress. High-intensity physical activity and regular exercise (23 days per week for 3060 minutes) were significantly associated with lower depression, anxiety, and stress levels. High internet use was significantly associated with increased stress. The findings indicate a high burden of psychological distress among Iraqi university students. Early screening and university-based mental health interventionsparticularly those targeting sleep hygiene, physical activity, and stress managementare urgently needed to support student well-being.